Inhibition of the JAK2/STAT3 Pathway Reduces Gastric Cancer Growth In Vitro and In Vivo - Judd, Louise M.; Menheniott, Treve R.; Ling, Hui; Jackson, Cameron B.; Howlett, Meegan; Kalantzis, Anastasia; Priebe, Waldemar; Giraud, Andrew S. (PLOS ONE, 2014)
Signal Transducer and Activator of Transcription-3 (STAT3) is constitutively activated in many cancers where it promotes growth, inflammation, angiogenesis and inhibits apoptosis. We have shown that STAT3 is constitutively activated in human gastric cancer, and that chronic IL-11-driven STAT3 transcriptional activity induces gastric tumourigenesis in the gp130757FF mouse model of gastric cancer development. Here we show that treatment of human AGS gastric cancer cells with the Janus Kinase (JAK) inhibitor WP1066 dose-, and time-dependently inhibits STAT3 phosphorylation, in conjunction with reduced JAK2 phosphorylation, reduced proliferation and increased apoptosis. In addition, application of intraperitoneal WP1066 for 2 weeks, reduced gastric tumour volume by 50% in the gp130757FF mouse coincident with reduced JAK2 and STAT3 activation compared with vehicle-treated, littermate controls. Gastric tumours from WP1066- treated mice had reduced polymorphonuclear inflammation, coincident with inhibition of numerous proinflammatory cytokines including IL-11, IL-6 and IL-1β, as well as the growth factors Reg1 and amphiregulin. These results show that WP1066 can block proliferation, reduce inflammation and induce apoptosis in gastric tumour cells by inhibiting STAT3 phosphorylation, and that many cytokines and growth factors that promote gastric tumour growth are regulated by STAT3-dependent mechanisms. WP1066 may form the basis for future therapeutics against gastric cancer.